Pengaruh Brand Image dan Digital Marketing Terhadap Purchase Intention Melalui Loyalitas Pelanggan Sebagai Variabel Mediasi - Yohanes Edo Yuliantoro; Henny Welsa; Agus Dwi Cahya (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This research aims to investigate the influence of brand image and digital marketing on purchase intention through loyalty as a mediating variable among Legend Coffee consumers. It employs a quantitative approach, sampling 120 customers from Legend Coffee in Yogyakarta using non-probability purposive sampling method. Data collection was conducted online via Google Form questionnaires. The findings indicate that (1) brand image does not have a significant positive effect on purchase intention. (2) Both brand image and digital marketing positively and significantly influence loyalty. (3) Loyalty does not significantly affect purchase intention. (4) Digital marketing has a positive and significant impact on purchase intention. Mediation analysis reveals that loyalty mediates the relationship between brand image and purchase intention, as well as between digital marketing and purchase intention. Future research could explore additional variables to enhance brand loyalty.